Poverty analysis in the lowlands of Papua New Guinea underscores climate vulnerability and need for income flexibility - Schmidt, Emily; Gilbert, Rachel; Holtemeyer, Brian; Mahrt, Kristi (Australian Agricultural and Resource Economics Society, 2021)
A severe El Niño event in 2015/16 decimated an important share of Papua New Guinea's (PNG) local crop production, leaving 10 per cent of the population with significant food shortages. Lack of recent socio‐economic data and analysis of the country's rural population impeded efforts to plan and mitigate the ensuing food crisis. This paper presents the most recent poverty analysis in Papua New Guinea in nearly a decade, and a renewed effort to inform rural production, consumption and livelihood patterns in some of the country's most remote, lowland areas. We designed a rural household survey that collected detailed consumption and expenditure data to explore poverty prevalence and correlates of per capita household expenditure. Results suggest that approximately half of the sampled individuals live in households with total per capita expenditures below the poverty line. Climate shocks have significant and possibly long‐term consequences for household welfare. Households that experienced a drought in the last 5 years are associated with significantly lower per capita expenditures. Labour diversification, via migration, is associated with greater welfare. Households with at least one migrant member are associated with 13 per cent greater per capita expenditure.